TINGKAT MOTIVASI SISWA PADA PENERAPAN PROSES PEMBELAJARAN PJOK OLEH GURU PLP PADA SMP NEGERI 23 SURABAYA - Nala Krisna, Arvie; Indahwati, Nanik (Samudra Publisher, 2025)
Education is a conscious process aimed at developing human potential both physically and mentally and must align with prevailing social values. One essential form of education is Physical Education, Sports, and Health (PJOK), which not only enhances students’ physical abilities but also supports their psychological development and character building. PJOK learning requires active student participation through enjoyable and meaningful physical activities. However, the success of the learning process largely depends on students’ learning motivation, which is the internal drive to engage actively in educational activities. In practice, this motivation is strongly influenced by the teacher’s role in delivering material and creating an engaging learning environment. Observations conducted at SMPN 23 Surabaya during the second semester of the 2024/2025 academic year revealed that most students showed low participation in PJOK lessons. Of the 30 students observed, only five actively responded to the teacher’s questions, while the rest appeared passive and easily distracted. The lack of motivation and quick onset of boredom suggest that the current teaching approach is ineffective. Therefore, innovation in PJOK learning models, particularly by PLP (Pre-Service Practice) teachers, is needed to enhance student interest and motivation. This study aims to examine the effect of PLP teachers' learning model implementation on student motivation in PJOK classes. The research employs an ex post facto method and uses the Alpha Cronbach formula to test the reliability of the motivation questionnaire.